Speech Delay in Toddlers: Encouraging Everyday Talking among Children - Mariyana, Rina; Febrina, Cory; Herwin, Maisie Alvina Azaria (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Delays or failures in language development that occur in children are caused by several reasons including poor hearing, incomprehensible speech, speech deficits and striking languageAims: The aim of this research is to explore the phenomenon of speech delays (Speech Delay) in toddler age children.Method: The research method used in this study is a qualitative method. Population of 10 respondents with inclusion criteria: Children who experience speech delays (Speech Delay) after screening the child's KTSP Language observation sheet at the age of 24 months to 36 months. Does not include children with special needs such as Down syndrome, autismResults: With in-depth interviews and the results obtained: children's difficulty in speaking, the emotional condition of children who experience speech delays, parenting patterns for children who experience speech delays and methods of stimulating children who experience speech delays. just the ends of words and limited vocabulary. Difficulty in responding to commands/instructions is illustrated by the situation where children, when given an order, just turn their heads, remain silent, don't understand and don't care. For this reason, there is a need for early detection in children with appropriate speech delay stimulation for children.